Modelling urban sprawl using remotely sensed data - Padmanaban, Rajchandar (2017)
Padmanaban, R., Bhowmik, A. K., Cabral, P., Zamyatin, A., Almegdadi, O., & Wang, S. (2017). Modelling urban sprawl using remotely sensed data: A case study of Chennai city, Tamilnadu. Entropy, 19(4), 1-14. [163]. https://doi.org/10.3390/e19040163